Implementasi PSAK 107 (Sewa Menyewa) pada Pencatatan Keuangan di Hotel Apri Inn Syariah Pangkalpinang - Ramadani, Mutiara; Rizki; Ulyah, Himmatul (PROGRAM STUDI AKUNTANSI SYARIAH FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2025)
This study aims to implement PSAK 107 in the financial records of the Apri Inn Syariah Pangkalpinang Hotel and identify obstacles in its implementation. The method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the recording of rental income transactions in hotels is still done manually and is not fully in accordance with PSAK 107, especially in the aspects of recognition, measurement, presentation, and disclosure of ijarah transactions. The main obstacles in implementing this standard include the lack of management understanding of sharia accounting, limited competent human resources, and the unavailability of a technology-based recording system. Therefore, it is recommended that hotels immediately implement financial records in accordance with PSAK 107 to improve transparency and accuracy of financial reports and ensure compliance with sharia accounting principles.